Peran Ruminasi terhadap Perilaku Non-suicidal Self-injury pada Remaja - Tamalo, Michael Suthirta; Arbi, Dian Kartika Amelia (Universitas Airlangga, 2024)
This study aims to examine the effect of rumination on NSSI behavior in adolescents. Rumination defined as repeated and persistent negative thoughts about distress, personal problems, and upsetting experiences, is one determinant of NSSI behavior, especially among adolescents. Rumination has 2 dimensions, reflection refers to a problem-solving process in which individuals attempt to make sense of negative feelings, while brooding is a passive comparison between one's situation and some unattainable standard. The study used a cross-sectional quantitative approach with a survey method on 112 respondents (46 male, 66 female). It was measured with RSS and the ISAS and analyzed using Pearson's r correlation technique and multiple linear regression analysis. The results showed that there was no role of reflection and there was a significant role of brooding as a predictor of NSSI behavior in adolescents. The coefficient model results state that reflection has no effect, while brooding has a significant effect in predicting NSSI behavior in adolescents.